The Evolution of English as a Global Lingua Franca: Historical Trajectories, Socio-political Forces, and Contemporary Implications - Dr. Chander Mohan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This paper examines the multifaceted rise of English as a global lingua franca, tracing its development from a regional Germanic dialect to the dominant medium of international communication. Drawing on historical linguistics, postcolonial theory, and contemporary sociolinguistics, the study maps three major phases of English expansion: the early modern period of colonial projection, the twentieth-century American cultural and economic diffusion, and the digital-era consolidation of English as the de facto language of global knowledge production. The paper argues that English dominance is not the inevitable outcome of intrinsic linguistic properties but rather the accumulated product of geopolitical power asymmetries, institutional entrenchment, and network effects. It further considers the tensions between global intelligibility and local linguistic identity, and outlines possible trajectories for the language in an era of artificial intelligence and multipolar global order.